2011
DOI: 10.1590/s1516-89132011000200016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oxidation of leaves of Ilex paraguariensis (St. Hil)

Abstract: This work aimed to study the oxidation of leaves of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Studies of physico-chemical characteristics and oxidation of the leaves have been performed (Molin et al, 2011;Dartora et al, 2011), usually by a similar process used in the obtaining of black tea from Camellia sinensis leaves. Studies about yerba-mate properties allied to its use as teas is a challenge, considering that the tea is the most consumed beverage in the world, after the water (Namita et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of physico-chemical characteristics and oxidation of the leaves have been performed (Molin et al, 2011;Dartora et al, 2011), usually by a similar process used in the obtaining of black tea from Camellia sinensis leaves. Studies about yerba-mate properties allied to its use as teas is a challenge, considering that the tea is the most consumed beverage in the world, after the water (Namita et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative process in yerba-mate leaves was previously utilized for the development of a functional beverage, similar to black tea obtained from Camellia sinensis leaves. 23,24…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative process in yerba-mate leaves was previously utilized for the development of a functional beverage, similar to black tea obtained from Camellia sinensis leaves. 23,24 The process reported here, in addition to promoting the washing of leaves, and possibly avoiding exposure to aromatic polycyclic hydrocarbons, can minimize the degradation of phenolic compounds presents in yerba-mate leaves. A previous study reported the high oxidation rate of 5-O-caffeoylquinic acid in the temperatures utilized in the conventional enzymatic inactivation and drying of yerba-mate leaves.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that L* value is negatively correlated with the total chlorophyl content. [26] In other words, the increase in L* value in the fermented MOS tea sample may be attributed to loss in chlorophyll content due to oxidative degradation along with the conversion of chlorophylls to pyropheophytin and pheophytin. [27] Meanwhile, the a* values seemed to suggest that as the teas were exposed to increasing degrees of fermentation, the greenness increased from À 4.79 for the nonfermented to À 4.97 and À 5.52 for the semi-fermented and fermented MOS tea materials, respectively.…”
Section: Physical Appearance Of Mos Teasmentioning
confidence: 99%